УМУМИНСОНИЙ ВА ДИНИЙ ҚАДРИЯТЛАР ДИАЛЕКТИКАСИ ЁШ АВЛОД ДУНЁҚАРАШИНИ ШАКЛЛАНТИРИШ ВА ЮКСАЛТИРИШДАГИ КОНЦЕПТУАЛ АҲАМИЯТИ - Эргашева, Г.М. (SCIENCE and SOCIETY, 2025)
The article emphasizes the conceptual significance of the dialectic of universal and religious values in the formation and improvement of the worldview of the younger generation. The greater part of the spiritual heritage and sacred values of our nation is made up of Islamic spirituality and education, such sources as the Holy Quran, Hadith, interpretations and rules of Sharia.
Keywords: value; nation; history; spirituality; worldview; attitude; idea; politics; culture